Lifting the Bar: A Relationship-Orienting Intervention Reduces Recidivism Among Children Reentering School From Juvenile Detention. (November 2021) - Walton, Gregory M.; Okonofua, Jason A.; Remington Cunningham, Kathleen; Hurst, Daniel; Pinedo, Andres; Weitz, Elizabeth; Ospina, Juan P.; Tate, Hattie; Eberhardt, Jennifer L.
When children return to school from juvenile detention, they face a severe stigma. We developed a procedure to orient educators and students toward each other as positive relationship partners during this period. In Study 1, through a structured exercise, students reentering school powerfully articulated to an educator of their choosing their prosocial hopes for school as well as challenges they faced. In a preliminary field trial ( N = 47), presenting this self-introduction to this educator in a one-page letter via a third-party requesting the educator's help reduced recidivism to juvenile detention through the next semester from 69% to 29%. In Study 2 (preregistered), the letter led experienced teachers ( N = 349) to express greater commitment to, anticipate more success for, and feel more love and respect for a student beginning their reentry into school, potentially initiating a better trajectory. The results suggest how relationship-orienting procedures may sideline bias and make school more supportive for students facing stigma.